The Privatization of Public Safety in Urban Neighborhoods: Do Business Improvement Districts Reduce Violent Crime Among Adolescents?. Issue 3 (22nd July 2013) - MacDonald, John; Stokes, Robert J.; Grunwald, Ben; Bluthenthal, Ricky
Abstract : The business improvement district (BID) is a popular economic development and urban revitalization model in which local property and business owners must pay an assessment tax that funds supplementary services, including private security. BIDs constitute a controversial form of urban revitalization to some because they privatize economic development and public safety efforts in public space. This study examines whether BIDs provide tangible benefits beyond their immediate boundaries to local residents in the form of reduced violence among adolescents. The empirical analysis advances an existing literature dominated by evaluation studies by introducing a theoretically driven dataset with rich information on individual and neighborhood level variables. The analysis compares violent victimization among youths living in BID neighborhoods with those in similarly situated non‐BID neighborhoods. We find no effect of BIDs on violence. However, we do find that youth violence is strongly correlated with neighborhood collective efficacy and family‐related attributes of social control. In conclusion, we argue that BIDs may be an agent of crime reduction, but this benefit is likely concentrated only in their immediate boundaries and does not extend to youths living in surrounding neighborhoods.